2017
DOI: 10.3390/ma10020114
|View full text |Cite
|
Sign up to set email alerts
|

Microcapsule-Type Self-Healing Protective Coating for Cementitious Composites with Secondary Crack Preventing Ability

Abstract: A microcapsule-type self-healing protective coating with secondary crack preventing capability has been developed using a silanol-terminated polydimethylsiloxane (STP)/dibutyltin dilaurate (DD) healing agent. STP undergoes condensation reaction in the presence of DD to give a viscoelastic substance. STP- and DD-containing microcapsules were prepared by in-situ polymerization and interfacial polymerization methods, respectively. The microcapsules were characterized by Fourier-transform infrared (FT-IR) spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Secondly, the low-temperature self-healing agent needs to be cured at low temperature after filling the damaged region. STP undergoes a condensation reaction of silanol end groups in the presence of DD at room temperature [ 25 ]. In this study, we investigated the low–temperature condensation reaction of STP ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the low-temperature self-healing agent needs to be cured at low temperature after filling the damaged region. STP undergoes a condensation reaction of silanol end groups in the presence of DD at room temperature [ 25 ]. In this study, we investigated the low–temperature condensation reaction of STP ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Linseed oil was applied to a petri dish and allowed to react for 7 days at room temperature (23)(24)(25)(26)(27) • C) or at −20 • C. Samples were collected periodically and analyzed by FT-IR spectroscopy [6,10]. The degree of conversion of C=C groups of linseed oil was analyzed by an IR band-ratio method.…”
Section: Reaction Conversion Measurementmentioning
confidence: 99%
“…To evaluate preliminarily the applicability of the linseed oil microcapsule-based self-healing coating system to cementitious composite materials, a water sorptivity test was conducted using coated mortar specimens ( Figure 5) [24,25]. Each specimen was prepared by application of the control or self-healing coating formulation to one rectangular side of a square column mortar and by scratching the coated surface of the mortar with two types of cutters.…”
Section: Water Sorptivity Testmentioning
confidence: 99%
“…Currently, there has been no research on self-healing coating for preservative-treated bamboo (and wood), although several studies on self-healing coating for steel or concrete have been reported [23,25,[31][32][33][34]. It is well known that the material properties of steel or concrete and bamboo are obviously different [35].…”
Section: Introductionmentioning
confidence: 99%